2022
DOI: 10.3390/nu14091911
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Canteen Menus and Dietary Habits and Intakes of University Students in Indonesia

Abstract: A comprehensive assessment of the dietary status of university students in Indonesia is lacking. Hence, this study aims to assess students’ dietary habits, status, and the nutritive value of meals offered at university canteens. This was a cross-sectional study based on the dietary habits of 333 students, 26 of whom were interviewed for the dietary survey. The nutritional value of canteen menus used by nearly half of the students (44%) was also examined. Most menus lacked macro and micronutrients (i.e., calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…A study conducted in 2020 during the COVID-19 pandemic found that nearly half of the participants opted for packed lunches for meals consumed outside the home [40]. Regarding the utilization of university canteens, findings from a study conducted in Indonesia indicate that over half of university students who dine away from home prefer to have their meals in the canteen [30]. Conversely, another study conducted at Polish universities found that only 35.5% of students and staff members regularly use the cafeterias daily or at least once a week [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in 2020 during the COVID-19 pandemic found that nearly half of the participants opted for packed lunches for meals consumed outside the home [40]. Regarding the utilization of university canteens, findings from a study conducted in Indonesia indicate that over half of university students who dine away from home prefer to have their meals in the canteen [30]. Conversely, another study conducted at Polish universities found that only 35.5% of students and staff members regularly use the cafeterias daily or at least once a week [28].…”
Section: Discussionmentioning
confidence: 99%
“…These needs hint at a larger issue of nutritional imbalance, which demands deeper exploration. For example, this exploration would entail scrutinizing specific dietary deficiencies or excesses contributing to this imbalance, alongside investigating underlying factors such as socioeconomic influences, cultural norms, and the accessibility of nutritious food options [ 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…59 Insufficient energy supply can cause malnutrition. 60,61 Carbohydrates are an important energy supply for animals. 62 Lack of proteins in food is a major cause of malnutrition in animals.…”
Section: Discussionmentioning
confidence: 99%
“…3(C)), as Rpd3 is a Drosophila histone deacetylase 58 that regulates epigenetic effects such as lifespan 59 . Insufficient energy supply can cause malnutrition 60,61 . Carbohydrates are an important energy supply for animals 62 .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous research that found that optimizing the nutritional profile of menus, labeling based on nutrient profiling, and promoting nutrition education can improve students' diets. (15). 2) Universities can provide free exercise programs for students, such as yoga, Pilates, or Zumba.…”
Section: Discussionmentioning
confidence: 99%